2019
DOI: 10.31254/phyto.2019.8307
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and antioxidant activity of Syzygium aromaticum, Mondia whitei, Carissa spinarum and Caesalpinia bonduc

Abstract: Caesalpinia bonduc, Mondia Whitei, Carissa spinarum and Syzygium aromaticum are four medicinal plants used alone or in combination in the production of traditional liquors in Togo to treat infertility, impotence and infections. They were selected on the basis of an ethnobotanical survey among Togolese traditional medicine practitioners to be evaluated for their toxicological effects and antioxidant properties. The phytochemical extraction was carried out on the powders of the roots, leaves and seeds of C. bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The radical scavenging and antioxidant activities, as well as the therapeutic potentials of M. whitei leaf and root extracts, have been reported (17,33). However, not much is known about the ethnopharmacological properties of the fruit extract.…”
Section: Discussionmentioning
confidence: 99%
“…The radical scavenging and antioxidant activities, as well as the therapeutic potentials of M. whitei leaf and root extracts, have been reported (17,33). However, not much is known about the ethnopharmacological properties of the fruit extract.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to many positive aspects such as its diversity, availability, low cost, efficacy and low side effects [8]. However, in low-income countries, traditional healers most often use plant extracts in the long and short term without knowledge of the toxic effects that these could cause [9]. This situation could most often lead to toxic effects especially on the liver [9; 10], or even to death [11].…”
Section: Introductionmentioning
confidence: 99%
“…In low-income countries where most of the population engage in herbal medicine, the use of plants remains traditional [ 23 ]. But, the scientific knowledge about biological properties of active compounds of these plants as well as the doses to be administered is ignored and most of the time this situation leads to treatment failures [ 24 ]. It has been demonstrated that many traditional beneficial herbs have genotoxic or systemic (liver and kidney) toxicity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%